Interlayer Structure Engineering of MXene‐Based Capacitor‐Type Electrode for Hybrid Micro‐Supercapacitor toward Battery‐Level Energy Density - Cheng, Wenxiang; Fu, Jimin; Hu, Haibo; Ho, Derek (Advanced science, 2021)
Micro‐supercapacitors are notorious for their low energy densities compared to micro‐batteries. While MXenes have been identified as promising capacitor‐type electrode materials for alternative zinc‐ion hybrid micro‐supercapacitors (ZHMSCs) with higher energy density, their tightly spaced layered structure renders multivalent zinc‐ions with large radii intercalation inefficient. Herein, through insertion of 1D core‐shell conductive BC@PPy nanofibers between MXene nanosheets, an interlayer structure engineering technique for MXene/BC@PPy capacitor‐type electrodes towards ZHMSCs is presented. Owing to simultaneously achieving two objectives: (i) widening the interlayer space and (ii) providing conductive connections between the loose MXene layers, enabled by the conductive BC@PPy nanospacer, the approach effectively enhances both ion and electron transport within the layered MXene structure, significantly increasing the areal capacitance of the MXene/BC@PPy film electrode to 388 mF cm−2, which is a 10‐fold improvement from the pure MXene film electrode. Pairing with CNTs/MnO2 battery‐type electrodes, the obtained ZHMSCs exhibit an areal energy density up to 145.4 μWh cm−2 with an outstanding 95.8% capacity retention after 25000 cycles, which is the highest among recently reported MXene‐based MSCs and approaches the level of micro‐batteries. The interlayer structure engineering demonstrated in the MXene‐based capacitor‐type electrode provides a rational means to achieve battery‐levelenergy density in the ZHMSCs. The demonstrated interlayer structure engineering synchronously realized the facilitated zinc‐ion and electron transfer kinetics between loose MXene nanosheets, resulting in enhanced charge storage capacity of MXene‐based capacitor‐type electrode toward hybrid micro‐supercapacitor with battery‐level energy density.